Formazione e società nella conoscenza Storie, teorie, professionalità. Atti del convegno di studi (Firenze, 9-10 novembre 2004) - Di Bello, Giulia (Firenze University Press, 2006)
The volume collects the Proceedings of the conference "Formazione e società della conoscenza. Storia, teorie, professionalità" ("Education and society of knowledge. History, theories, professionalisms), which took place in Florence on November 9 and 10, 2004 on the occasion of the 80th anniversary of the University of Florence. The conference dealt with rethinking the history of the Faculty of Education together with education issues arising in the current phase of rethinking the organisation of university studies. The four sessions of the conference dealt with topics such as: the history of the Faculty and the education of teachers and professors; education processes, models and theories; some concepts / focuses of education and the professional skills offered by the Faculty.